Cloud Computing Big Data Application Research Based on Blockchain Technology. Issue 3 (August 2021) - Han, Shuhe; Chen, Zhenjiang
Abstract: In the application process of cloud computing technology based on blockchain technology, due to the high similarity between cloud computing technology and blockchain technology at the network architecture level and technology application mode level, the two technologies can be reasonably integrated to allow customers to cut relevant data and distribute such fragmented data to the whole blockchain system for storage [1]. In view of the complexity of "blockchain" technology and the humanistic thinking it brings, it is a subversive revolution for the existing society, whether at the level of technology or the level of people to people values. Combining it with cloud computing big data can highlight the role of both.